Locus of control in health and self-esteem in type-2 diabetic patients - Fuscaldi, Fernanda Silva; Balsanelli, Alessandra Cristina Sartore; Grossi, Sonia Aurora Alves (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to relate the scores obtained with the application of the scales of locus of control of health and self esteem with socio-demographic and clinical variables, risk factors and chronic complications in 65 patients with type-2 diabetes mellitus. This is a descriptive cross-sectional study. Statistical analysis was performed using Pearson's chi-square, Mann-Whitney, Kruskal-Wallis, and Spearman's Correlations tests. Regarding the locus of control, in average, patients presented higher scores in the internal dimension, and women showed more externality-at random for health. Statistically significant relationships were found between internality with time of diagnosis and physical activity; between externality-other powerful entities with glycated hemoglobin and physical activity; and between externality-at random with practice of physical activity. Most individuals has high self-esteem, but no variable was statistically related.